PENSION SYSTEM REFORM IN UKRAINE - Драхан, О.; Рыбак, Н. (SWorldJournal, 2021)
The article analyzes the features of reforming the domestic pension system, identifies the main problems of its implementation. The author describes the modern pension system in Ukraine; changes of interpretation are revealed and differences and innovatio